2016
DOI: 10.1002/ccr3.657
|View full text |Cite
|
Sign up to set email alerts
|

Multiple endocrine neoplasia phenocopy revealed as a co‐occurring neuroendocrine tumor and familial hypocalciuric hypercalcemia type 3

Abstract: Key Clinical MessageFamilial hypocalciuric hypercalcemia type 3 should be considered as differential diagnosis in patients with suspected primary hyperparathyroidism and/or suspected multiple neoplasia syndrome, as correct diagnosis will spare the patients for going through multiple futile parathyroidectomies and for the worry of being diagnosed with a cancer susceptibility syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…Our findings do not allow for such conclusions due to the small number of patients, although our findings of possible hypercalcemic symptoms in one of the identified families do support that FHH3 may be associated with more symptoms than FHH1. Furthermore, we found a p.Arg15His mutation in AP2S1 in a patient clinically suspected of having MEN1, but concluded that he was probably an example of a phenocopy (36). However, further studies of co-morbidities are warranted to establish whether these reported diseases are chance findings or actual complications associated with FHH3.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our findings do not allow for such conclusions due to the small number of patients, although our findings of possible hypercalcemic symptoms in one of the identified families do support that FHH3 may be associated with more symptoms than FHH1. Furthermore, we found a p.Arg15His mutation in AP2S1 in a patient clinically suspected of having MEN1, but concluded that he was probably an example of a phenocopy (36). However, further studies of co-morbidities are warranted to establish whether these reported diseases are chance findings or actual complications associated with FHH3.…”
Section: Discussionmentioning
confidence: 81%
“…As we have previously reported (36), the index patient with the p.Arg15His mutation also had a family history of hypercalcemia believed to be a genetically unverified multiple endocrine neoplasia syndrome (MEN1), but went through multiple parathyroidectomies before the diagnosis of FHH3 was reached (36). Two hypercalcemic and five normocalcemic family members were screened for the p.Arg15His mutation, which resulted in the confirmation of the co-segregation of the c.44G > A genotype with hypercalcemia.…”
Section: Patients With Mutation In Ap2s1mentioning
confidence: 94%
See 1 more Smart Citation
“…(50). Pelos nossos resultados, casos com estes fenótipos que forem plenamente investigados e que resultarem negativos para mutação germinativa representariam casos anedóticos que seriam candidatos fortes para investigação de outros genes por exomas/genomas ou para outros eventos muito raros de tumorigênese como mosaicismo (54,116). Além disso, casos anedóticos de MEN1(-) foram descritos apresentando mutações germinativas nos genes CASR e AP2S1 associados com fenótipo de hipercalcemia hipocalciúrica familial (FHH) e no gene CDC73 responsável pela síndrome de HPT associado a tumor de mandíbula (HPT/JT) (50, 60-61, 108, 116).…”
Section: Algoritmos Clínicos De Predição Para Presença/ausência De Mu...unclassified